Case Report: Iatrogenic Dental Progress of Phantom Bite Syndrome: Rare Cases With the Comorbidity of Psychosis - Watanabe, Motoko; Hong, Chaoli; Liu, Zhenyan; Takao, Chihiro; Suga, Takayuki; Tu, Trang Thi Huyen; Yoshikawa, Tatsuya; Takenoshita, Miho; Sato, Yusuke; Higashihori, Norihisa; Moriyama, Keiji; Motomura, Haruhiko; et al. (Frontiers in Psychiatry, 2021)
Introduction: Phantom bite syndrome (PBS) is considered as the preoccupation with dental occlusion and the continual inability to adapt to changed occlusion. These patients constantly demand occlusal corrections and undergo extensive and excessive dental treatments. We present 3 cases with PBS-suspected iatrogenic concerns and the attribution to underlying psychosis. Case presentation: A 70-year-old female demanded orthodontic retreatment and complained of tightness and cramped sensation of teeth in the oral cavity, uncomfortable occlusion, and pain in her neck and legs that she was convinced was induced by orthodontic treatment. However, even earlier than the orthodontic treatment, she had kept doctor shopping for over 35 years, not merely dentists but also psychiatrists, neurologists, and so on; she was diagnosed with bipolar disorder. A 48-year-old female complained of malaligned improper occlusion and demanded occlusal adjustment. These symptoms occurred in the absence of a dental trigger and were worsened by orthodontic treatment. She underwent the psychiatric treatment for 15 years with a diagnosis as bipolar disorder. A 38-year-old female, who had a history of schizophrenia for over 20 years, complained of occlusal discomfort and revisited with a complaint of abnormal occlusion due to excessive dental procedures. In last two cases, requests for dental procedures had reduced owing to the collaboration between the psychiatrists and dentists. All the cases first visited our clinic following a succession of dental visits. They were strongly convinced that occlusal correction was the only solution to their symptoms, including the symptoms of discomfort in other body parts. Their misleading perceptions were uncorrectable, and repeated dental treatments exacerbated their complaints. Moreover, the dentists overlooked the patient’s psychotic histories, while the comorbid psychosis resulted in a strict demand for dental treatment by the patients. Conclusions: The presented PBS cases with psychosis suggest that repeated dental treatments and comorbid psychosis exacerbate PBS. Moreover, their persistent demands reflecting comorbid psychosis led dentists to perform numerous procedures. Early detection of underlying psychosis and the prompt collaboration between psychiatrists and dentists are integral to help preventing complications in PBS cases with psychosis.